Advances in Organic Synthesis: Volume 14 - Atta-ur-Rahman (Bentham Science Publishers, 2021)
Advances in Organic Synthesis is a book series devoted to the latest advances in synthetic approaches towards challenging structures. The series presents comprehensive reviews written by eminent authorities on different synthetic approaches to selected target molecules and new methods developed to achieve specific synthetic transformations or optimal product yields. Advances in Organic Synthesis is essential for all organic chemists in academia and the industry who wish to keep abreast of rapid and important developments in the field. This volume presents the following chapters: -